High Value Care for Older Adults with Complex Care Needs: Leveraging Nurses as Innovators - Demiris, George (Nurs Outlook, 2019)
BACKGROUND: Our health care system is facing unprecedented and complex challenges in caring for older adults and their families. A paradigm shift is needed that recognizes new roles and competencies for nurses to play a leadership role in the design and implementation of high value care models. PURPOSE: The purpose of this paper is to introduce a series of recommendations for leveraging nurses to generate innovative tools and solutions for the delivery of value-based care for older adults living with complex health and social needs and their families. METHODS: These recommendations were generated by a Think-Tank of national experts based on review of current evidence and focus groups with older adults. DISCUSSION: The generated recommendations focus on positioning nurses to assume leadership roles in implementing evidence-based care models, preparing nurses to serve as health innovators and catalysts of system transformation, and fostering system-level infrastructure that leverages the contributions of nurses for current and emerging roles. CONCLUSION: Nurses as innovators can address the challenges in providing high quality care for older adults with complex needs and their families. System-level infrastructure, including resources for training and implementation of well-established programs, is necessary to leverage the contributions of nurses and facilitate innovative approaches to care.